La edición de literatura en la Argentina de fines de los sesenta - José Luis de Diego (Cuadernos LIRICO)
The study proposes a concise characterization of the book industry in the literary field during the late 1960s: cycles in book production, printed copies, print runs, exported volumes. It analyses the reasons for the publishing boom known as the «Argentine-book boom»: the possible causes for the demand of a new reading public, and its effects on the commercialization of published matter and on the professionalization of writers. On the basis of the data-gathering of book titles published between 1966 and 1970, the main houses’ publishing policies are characterized, from those consolidated in the 1930s (Sudamericana, Losada, Emecé) to those emerging in the studied period (Centro Editor de América Latina, Jorge Álvarez, De la Flor, Galerna, Tiempo Contemporáneo).